Formation of linear and cyclic polyoxetanes in the cationic ring‐opening polymerization of 3‐allyloxymethyl‐3‐ethyloxetane and subsequent postpolymerization modification of poly(3‐allyloxymethyl‐3‐ethyloxetane). Issue 5 (22nd December 2012) - Schulte, Bjoern; Dannenberg, Carl A.; Keul, Helmut; Möller, Martin
Abstract The synthesis of 3‐allyloxymethyl‐3‐ethyloxetane (AllylEHO) and its polymerization with BF3 × Et2O is described in this study. Size exclusion chromatography (SEC) and membrane osmometry are used for the determination of molecular weights of the obtained products, ranging from Mn, SEC = 41, 500‐131, 500 g/mol. 1H NMR spectroscopy, SEC, as well as MALDI‐TOF MS reveal the formation of cyclic tetramer beside low, but detectable concentrations of larger cyclic oligomers as by‐products during the polymerization process. These results help to understand mechanistically why attempts for a controlled homopolymerization of AllylEHO fail and why a controlled homopolymerization of oxetanes has not been described so far in the literature. Additionally, the high versatility of allyl‐functional polyoxetane for postpolymerization modification is proven by thiol–ene reactions with 3‐mercaptopropionic acid and N‐acetyl‐L‐cysteine methyl ester. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013